2020
DOI: 10.1155/2020/2902498
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Anemia in Pregnancy: Findings from the Ethiopian Health and Demographic Survey

Abstract: In Ethiopia, anemia during pregnancy is a major public health problem and affects both the mother’s and their child’s health. There is a scarcity of community-based evidence on determinants of anemia among pregnant women in the country. Therefore, this study aimed to assess the determinants of anemia among pregnant women in Ethiopia. Method. This study was based on the 2016 Ethiopian Demographic Health Survey (EDHS) that used a two-stage stratified cluster sampling technique. A cross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
22
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 20 publications
(21 reference statements)
7
22
1
4
Order By: Relevance
“…This condition is quite worrying, so it needs actions and research studies that can be used to overcome this problem. A study conducted by Woldegebriel et al found that the maternal age, education, family income, religion, number of family members at home, and number of children were determinant factors that contribute to anemia in pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is quite worrying, so it needs actions and research studies that can be used to overcome this problem. A study conducted by Woldegebriel et al found that the maternal age, education, family income, religion, number of family members at home, and number of children were determinant factors that contribute to anemia in pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were contrasting reports from other African studies from Ethiopia and Nigeria, where the highest prevalence was reported among participants of the age group 30-39 years in Ethiopia and the Nigerian study reported the highest prevalence among participants in the age group of 20years and below (9,17). This might have been because of increased body weakness, multiple pregnancies, labour, and being subjected to other illnesses leading to a predisposition to anaemia as age advances (9,26). This study reported anaemia prevalence higher among women living in the urban area (27.6%) than women living in rural areas (15.5%).…”
Section: Discussionmentioning
confidence: 90%
“…High prevalence in younger ages might have been due to the lack of awareness, poor knowledge of antenatal services, and failure to seek prenatal care early and take care of themselves during pregnancy (5,17). However, there were contrasting reports from other African studies from Ethiopia and Nigeria, where the highest prevalence was reported among participants of the age group 30-39 years in Ethiopia and the Nigerian study reported the highest prevalence among participants in the age group of 20years and below (9,17). This might have been because of increased body weakness, multiple pregnancies, labour, and being subjected to other illnesses leading to a predisposition to anaemia as age advances (9,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe requirements increase exponentially during pregnancy to meet the increased demand for the fetoplacental unit, increase maternal erythrocyte mass and compensate for Fe loss during labor [10], [11]. A study found that maternal age, education, family income, religion, number of family members at home, and children's number were determinants that contributed to anemia [12]. Postpartum maternal anemia may be associated with shortness of breath, lethargy, infection, lactation failure, and depression [13], [14].…”
Section: Introductionmentioning
confidence: 99%